Things I know about love - Le Vann, Kate. (New York : Egmont USA, 2010)
Seventeen-year-old Livia Stowe travels from England to Princeton, New Jersey, to visit her brother who is studying there and to celebrate her recovery from a year-long struggle with leukemia, and while she is there she writes a blog about her experiences, which include falling in love.
Keywords: British -- United States -- Fiction; Dating (Social customs) -- Fiction; Leukemia -- Fiction; Brothers and sisters -- Fiction; Blogs -- Fiction; Princeton (N.J.) -- Fiction; British -- United States -- Juvenile fiction; Dating (Social customs) -- Juvenile fiction; Leukemia -- Juvenile fiction; Siblings -- Juvenile fiction; Blogs -- Juvenile fiction; Princeton (N.J.) -- Juvenile fiction